Successful accessory renal artery denervation in a patient with resistant hypertension - (:unkn) unknown (My University, 2014)
Renal sympathetic denervation is safe and effective in patients with resistant hypertension. In all of the studies of renal artery denervation, patients with accessory renal arteries are excluded. So there is not any data regarding renal sympathetic denervation applied to the accessory renal arteries. We present a young female patient with resistant hypertension despite use of five different antihypertensive drugs. The patient had a well developed (diameter >4 mm) left renal accessory. We believe that if we omitted the well developed accessory renal artery, we would not have maintained adequate blood pressure control. Thus, we applied radiofrequency ablation to both renal arteries and left accessory artery. Immediately after the procedure, the patient's blood pressure was reduced to 110/60 mmHg and this effect was continued during the first month of follow-up.
Keywords: Accessory renal artery; renal sympathetic denervation; resistant hypertension